Congenital nodular fasciitis: an extremely rare entity with review of literature - Till Wagner; Dietmar Ulrich (SpringerOpen, 2022)
Abstract Background Nodular fasciits is thought to be a benign superficial nodular disease, which most often occurs in the medium age of adolescence, mainly in the subcutaneous or fascial plane on the upper extremities and trunk. The percentage of this entity in children compared to adults is less than 10%. Most cases in childhood were reported at the head and neck region, therefore often renamed to cranial or extracranial fasciitis. These lesions often consists of sarcoma like structures. Preoperative imaging is often unspecific and the standard of treatment in children is biopsy or in some cases complete resection with narrow margin depending on size or location of the lesion. Case presentation We present a clinical case of a female newborn with a congenital nodular presternal mass. Biopsy revealed nodular fasciits by testing on USP6 gen rearrangement. With ongoing growth of her nodular thoracic tumor, she underwent complete resection with primary closure. We followed her clinical course over more than 3 years and give a review of the literature. Conclusion Only a minority of reports are documented with a neonate onset and none with a real congenital. We hereby presented the first case in literature of a proven congenital fasciits other than cranial/extracranial in a newborn and her clinical course.